PMO-028 The potential of soup and savoury drinks for oral hydration in short bowel syndrome with jejunostomy. (28th May 2012) - Turner, P
Abstract : Introduction: Patients with short bowel syndrome (SBS) and a jejunostomy are required to drink unpalatable electrolyte solutions. This is because the jejunal mucosa is permeable to sodium (Na) and whenever fluids containing <90 mmol/l Na are present in the lumen, water and Na are lost by diffusion leading to massive stoma losses. Patients are advised to consume 1000 mls of a glucose/saline electrolyte solution with >90 mmol/l Na while restricting other fluids to around 500 mls/day. 1 Electrolyte solutions are unpalatable and compliance is often poor. Although glucose is a significant component of these solutions due to coupled absorption of glucose, Na and water, a high Na content is of primary importance as there is considerable passive diffusion of Na and water across concentration gradients between the jejunal lumen and plasma. 2 Soups and meat extracts are high in Na but appear to be a relatively unused resource in SBS. This may be because health professionals are unaware of their Na content. A survey of such products was carried out to see if their Na content was high enough to replace some or all of the usual electrolyte drinks. Methods: Manufacturers UK websites were accessed to obtain the Na and fibre content of four brands of tinned soups (Heinz, Baxter's, Campbell's and Sainsbury's), four brands of instant cup soup (Bachelor's, Tesco, Campbell's and Ainsley Harriott) and one brand of meat extract (Bovril). Results: Results were obtained for 57 samples of tinned soup, 48 samples of cup soup and two meat extracts. Na content of soups reconstituted as per manufactures recommendations. Na concentrations of beef and chicken extracts were 96 and 156 mmol/l respectively when made up as 12 g in 250 mls water. Mean fibre content for tinned soup and cup soup was 0.65 g and 0.6 g per 100 ml respectively (range 0–3.3 g/100 ml). Conclusion: The majority of products investigated contain >90 mmol/l Na and are suitable for consumption by patients with jejunostomies. Patients can be advised to check food labels for products containing >0.21 g Na/100 ml (91 mmol/l). Fibre content of soup is relatively low however patients can be advised to seek lowest fibre varieties if this is an issue. In conclusion, soups or meat extracts could be considered as a partial replacement for electrolyte drinks where compliance is poor, provided there is careful initial monitoring of fluid balance and biochemistry. Competing interests: None declared. References: 1. Nightingale J, Woodward JM; On behalf of the Small Bowel and Nutrition Committee of the BSG 2006. Guidelines for management of patients with a short bowel. http://www.gut.bmjjournals.com 2. Fordtran JS, et al. The mechanisms of sodium absorption in the human small intestine. J Clin Invest 1968;47 :884.